Comparative evaluation of microbial translocation products (LPS, sCD14, IgM Endocab) in HIV-1 infected Indian individuals. (October 2017) - Negi, Neema; Singh, Ravinder; Sharma, Ashutosh; Das, Bimal Kumar; Vajpayee, Madhu
Abstract: Background: Microbial translocation of lipopolysaccharides (LPS), soluble CD14 (sCD14) and IgM Endocab levels have been reported to be associated with disease progression in HIV-1 infection. In this longitudinal study, plasma levels of different microbially translocated products (LPS, sCD14, Endocab) was investigated in HIV-1 infected Indian Individuals stratified as Rapid (R), Viremic slow (VS), Slow progressors (S) and healthy controls. Method: Ten healthy and twenty HIV-1 infected individuals were enrolled. Plasma levels of LPS, sCD14, Endocab was examined using commercially available Limulus Amebocyte assay and enzyme-linked immunosorbent assay (ELISA) enzyme linked immunosorbant assay. Results: Elevated levels of sCD14, IgM EndoCab and LPS were observed during HIV-1 infection compared to healthy controls. Rapid progressors had higher levels of sCD14, IgM EndoCab, LPS (median% 1553, 3596, 202.2) compared to viremic slow, slow progressors and healthy controls both at baseline and follow up visits. At baseline, LPS correlated positively with IgM Endocab and negatively with sCD14 levels while at follow-up, significant positive correlation was observed between IgM Endocab and sCD14 (IgM EndoCab r = 0.490, p = 0.05; sCD14 r = 0.051, p = 0.830). Plasma levels of sCD14 correlated positively with viral load in rapid, viremic slow and slow progressors while CD + T cell count correlated positively with sCD14 and IgM EndoCab levels in viremic slow and slow progressors. Conclusion: Our findings indicate that elevated levels of sCD14, IgM EndoCab and LPS in HIV-1 infected individuals are strong predictors of disease progression and could be considered as candidate biomarkers for disease monitoring. Highlights: Elevated levels of LPS, sCD14 and IgM Endocab were found in HIV-1 infected Indian Individuals. Levels of microbial translocation products was found to be high in rapid progressors. Plasma viral load correlated positively with soluble markers. Microbial translocation products are good predictors of disease progression.